Percy Jackson and the last Olympian - Riordan, Rick (Puffin books: London, 2013)
"Most people get presents on their sixteenth birthday. I get a prophecy that could save or destroy the world. That's how it is when you're the son of Poseidon, God of the Sea. According to an ancient prophecy, bad things will happen when I turn sixteen - because I'm the one who gets to decide the fate of the entire world. But no pressure. This is the one where Kronos, Lord of the Titans, is beginning his attack on New York City, where Mount Olympus stands virtually unguarded. Oh, and the dreaded (and not to mention enormous) monster Typhon is also heading our way. So it's me and forty of my demigod friends versus untold evil..."
Keywords: English, Fiction